Further studies on the role of the residue 890 cysteine to tyrosine mutation in the M70 primase ORF of the temperature‐sensitive mutant (tsm5) of murine cytomegalovirus. Issue 9 (8th March 2016) - Al‐Ali, Abdulaziz Taher; Sweet, Clive
Abstract : A mutation (C890Y) introduced into the M70 primase gene of murine cytomegalovirus (MCMV) resulted in reduced viral replication in murine embryo fibroblasts at 40°C and the mutant was severely attenuated in vivo. The attenuated replication of the M70 mutant was also observed in Raw 264.7 macrophages at 37°C, demonstrating that the mutation produced a defective rather than an unstable protein possibly reducing the amount of functional protein under different environmental conditions. Many synonymous mutations were introduced into this ORF by changing codon preferences that should reduce the efficiency of gene translation, but not change protein sequence or structure. Two Bacterial Artificial Chromosome (BAC) constructs were produced with 155 codons (at the distal third of the M70 gene) changed to MCMV less preferred codons and with either cysteine (BAC70 155Cys ) or tyrosine (BAC70 155Tyr ) at residue 890. Upon transfection of these BACs into NIH 3T3 cells, only BAC70 155Cys produced virus and this mutant Mt70 155Cys replicated similarly to its revertant and the wt MCMV K181 (Perth) variant. A metagenomic analysis of the protein structure of the primase using PredictProtein showed that the change from cysteine (M70Cys) to tyrosine (M70Tyr) has a marked effect on protein structure. However, when the cysteine residue was replaced by serine (M70Ser) or methionine (M70Met), which produced mutant viruses with a wild‐type phenotype, the predicted structure was similar to the wild‐type structure. J. Med. Virol. 88:1613–1621, 2016 . © 2016 Wiley Periodicals, Inc.